Renegotiating the KOREA-US FTA. American Hegemony and the - Lee Hae-young (Asia-Pacific Journal, 2010)
On December 3, 2010 South Korea and the United States announced that they had reached agreement on a new KOREA-US FTA with comprise agreements on both automobiles and agriculture. The agreement may face difficult hurdles in the legislatures of both countries that must ratify it. This article examines the process and politics that led to the agreement.Whether the Free Trade Agreement reached between South Korea and the United States (KORUS FTA) prior to the November 12 Seoul G20 Summit constituted a hasty "renegotiation" of the 2007 Treaty to comply with US demands on the eve of President Barak Obama's visit to Seoul, is no longer just a matter of semantics. Of course, it is apparent why the Lee Myung-bak administration -- as well as certain news outlets under its influence -- has doggedly insisted on referring to the negotiations by a different name. First, this was to hide the fact that the administration's declaration of "no renegotiation" had failed. Second, it was a kind of ploy to avoid a National Assembly review, the argument being that no such review was required since this was not "renegotiation." However hard the Lee administration has worked to conceal it, the U.S. press with its freedom of speech has provided a detailed account of virtually all matters. And one can even find a fair amount of information trickling through the South Korean press as well.It took fierce resistance to renegotiation in South Korea to prevent the two presidents from announcing the conclusion of the FTA as planned during Obama's visit to Seoul for the G20 Summit.